Penguatan Kecerdasan Spiritual Peserta Didik Melalui Pembelajaran Alquran Hadits Di Madrasah Ibtidaiyah - Irma Fauziah Irma (JURNAL ILMIAH INNOVATIVE (Jurnal Pemikiran Dan Penelitian), 2021)
The recent moral degradation, especially among students, with several various cases shows the need to strengthen spiritual intelligence as a fortress for strengthening aqidah and morals for the nation's future generations. The role of education is of course very crucial in this case, one of which is Islamic Religious Education. The implementation of the Hadith Qur'an Learning in Islamic elementary school contains the objectives and scope according to the indicators of one's spiritual intelligence. The purpose of this study was to analyze the character of the Alquran Hadith learning as a strengthening of the spiritual intelligence of students at Madrasah Ibtidaiyah. This research uses qualitative research methods with the type of library research. Sources of data used in this research are books, journals, articles and other relevant scientific works. The data were collected and then carried out a descriptive analysis